Women and Biotechnology's Pledges: Colonial Legacy and Postcolonial Biologics (International Journal of Innovative Research in Computer Science & Technology, 2021)
Feminist science and technology studies  have influenced our developing knowledge of sex,  gender, and biotechnology for three decades. We tend to  think of sex and gender in binary terms, which  significantly limits our understanding of human variety as  well as advances in science and technology. The Indian  Genome Variation Project and transnational surrogacy are  used as case studies in this article to examine how  popular biotechnology views are reduced to binary  stances that promote and oppose biotechnology as a  solution for India's economic and social progress. The  article contends that the effect of surrogacy and genomics  on women and gender is much more complicated since  they are situated within the broader geopolitical,  historical, economic and cultural changes of postcolonial  India. What is it about technology that makes it a  significant source of future hope? Is it because of  genomics' promise of excellent health that it has become  the location for such promises? Why has India become a  popular destination for transnational surrogacy and other  forms of reproductive tourism? For this reason, the article  makes a case for the social studies of science to show that  technology and human beings are never really neutral.  These colonial and postcolonial histories of science and  technology should inform our understanding of surrogacy  and genomics.
Keywords: Colonial; Gender; Genomics; Transnational Surrogacy; Women